I want to show that the smooth surface $$(x^2+y^2+z^2+a^2-b^2)^2=4a^2(x^2+y^2) , \text{ where } a>b>0$$ is the torus $$\sigma (\theta , \phi )=((a+b\cos \theta )\cos \phi , (a+b\cos \theta )\sin \phi , b\sin \theta )$$

For the one direction we set $$x=(a+b\cos \theta )\cos \phi \\ y=(a+b\cos \theta )\sin \phi \\ z=b\sin \theta $$ and show that it satisfies the equation $(x^2+y^2+z^2+a^2-b^2)^2=4a^2(x^2+y^2)$ right?

For the other direction:

We set $$x=(a+b\cos \theta )\cos \phi \\ y=(a+b\cos \theta )\sin \phi $$ and we suppose that the equality $$(x^2+y^2+z^2+a^2-b^2)^2=4a^2(x^2+y^2)$$ stands, then we get the following:

$$(((a+b\cos \theta )\cos \phi )^2+((a+b\cos \theta )\sin \phi)^2+z^2+a^2-b^2)^2=4a^2(((a+b\cos \theta )\cos \phi )^2+((a+b\cos \theta )\sin \phi)^2) \\ \Rightarrow ((a+b\cos \theta )^2 \cos^2 \phi +(a+b\cos \theta )^2 \sin^2 \phi+z^2+a^2-b^2)^2=4a^2((a+b\cos \theta )^2 \cos^2 \phi +(a+b\cos \theta )^2 \sin^2 \phi )\\ \Rightarrow ((a+b\cos \theta )^2 +z^2+a^2-b^2)^2=4a^2(a+b\cos \theta )^2 \\ \Rightarrow (a+b\cos \theta )^2 +z^2+a^2-b^2=\pm 2a(a+b\cos \theta ) $$

From $z^2=\pm 2a(a+b\cos \theta ) -(a+b\cos \theta )^2-a^2+b^2$ we get

$ {\tag 7}$

$$z^2= 2a(a+b\cos \theta ) -(a+b\cos \theta )^2-a^2+b^2 \\ \Rightarrow z^2=2a^2+2ab\cos \theta -a^2-2ab\cos \theta -b^2\cos^2 \theta -a^2+b^2 \\ \Rightarrow z^2= -b^2\cos^2 \theta +b^2 \\ \Rightarrow z^2= -b^2(1-\sin^2 \theta ) +b^2 \\ \Rightarrow z^2=b^2\sin^2 \theta \Rightarrow z=\pm b\sin \theta $$


$ {\tag 8}$

$$z^2= -2a(a+b\cos \theta ) -(a+b\cos \theta )^2-a^2+b^2 \\ \Rightarrow z^2=-2a^2-2ab\cos \theta -a^2-2ab\cos \theta -b^2\cos^2 \theta -a^2+b^2 \\ \Rightarrow z^2= -4a^2-4ab\cos \theta -b^2\cos^2 \theta +b^2 \\ \Rightarrow z^2= -(2a+b\cos \theta)^2 +b^2$$


But how do we get only $z=b\sin \theta$ ?


Squaring and square-rooting is a common pitfall.

$$ (a+b\cos \theta )^2 + z^2 +( a^2- b^2) >0 $$

It must be always positive because you had tacitly/implicitly assumed major radius of torus bigger than tube radius $ a>b. $

Taking negative sign would attempt to validate a physically impossible toroid, the negative sign at $(8)$ should be discarded whenever a spurious solution got in by the squaring process.

Else all ok.

  • $\begingroup$ I got it!! Thanks a lot! :-) $\endgroup$ – Mary Star Jan 7 '16 at 19:23
  • $\begingroup$ You are welcome.. $\endgroup$ – Narasimham Jan 7 '16 at 19:28

For the other direction you cannot set $$x=(a+b\cos \theta )\cos \phi \\ y=(a+b\cos \theta )\sin \phi $$ because that already assumes the wanted representation for all points $(x, y, z)$ on the surface. But if you do so then in your calculation at the step

$$ (a+b\cos \theta )^2 +z^2+a^2-b^2=\pm 2a(a+b\cos \theta) $$

you cannot have the minus-sign because the left-hand side is non-negative. That excludes the second case in your proof.

I would proceed as follows. With polar coordinates $$ x = r \cos \phi \, , \quad y = r \sin \phi \label 1\tag 1 $$ the equation becomes $$ (r^2 + z^2 + a^2- b^2)^2 = 4 a^2 r^2 \\ \Longleftrightarrow r^2 + z^2 + a^2- b^2 = \pm 2 a r $$

From $a > b$ it follows that we must have "$+$" on the rhs, and then the equation can be simplified to $$ (r - a)^2 + z^2 = b^2 $$ That is the equation of a circle and can be parameterized as $$ r - a = b \cos \theta \, , \quad z = b \sin \theta \label 2\tag 2 $$

Combining $(\ref{1})$ and $(\ref{2})$ gives the desired representation for $(x, y, z)$.

  • $\begingroup$ I understand!! Thanks for your answer!! :-) $\endgroup$ – Mary Star Jan 7 '16 at 19:23
  • 1
    $\begingroup$ @MaryStar: You are welcome! $\endgroup$ – Martin R Jan 7 '16 at 19:24

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.